Chemical Synthesis of 6-Azido-6-Deoxy Derivatives of Phosphatidylinositol Containing Different Fatty Acid Chains - Mosidur Rahaman Molla; Palak Gupta; Rajendra Rohokale; Zhongwu Guo (Molecules)
This paper describes the synthesis of two 6-azido-6-deoxy derivatives of phosphatidylinositol (PI), which contained different fatty acid chains. These syntheses, starting from methyl α-d-glucopyranoside, employed multiple regioselective transformations with Ferrier rearrangement as one of the key steps. The PI derivatives contained different fatty acid chains in the lipids and an azido group in the inositol residue to facilitate their further functionalization under bioorthogonal conditions. Therefore, they should be useful probes for the investigation of PI and related biology, such as PI phosphorylation, PI interaction with other molecules in cells, and the functions of lipid structures in these processes.